2016
DOI: 10.1109/ted.2015.2504105
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Thin Films Functionalized via Loading of Au Nanoclusters for Flexible Gas Sensors Devices

Abstract: Carbon nanotubes (CNTs) have been demonstrated to be one of the most interesting materials for gas sensing. This paper applies a simple method for the direct transfer of highdensity CNTs from a SiO 2 /Si substrate to a flexible substrate for carbon dioxide (CO 2 ), ammonia (NH 3 ), and isopropyl alcohol gas sensing at room temperature. The flexible gas sensor exhibited high sensitivities of 4.8%, 5.4%, and 5.2% at room temperature for ambient CO 2 , NH 3 , and isopropyl alcohol gas concentrations of 800 ppm, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…From the table above, we infer that our values of sensitivity (41-171.5) for the sensor containing Pt/MWCNTs (at 250 • C) are much higher than these previously reported in literature (0.025-10) for CNT based systems decorated with other metallic NPs. According to Young and Lin et al [16,17], Au NPs can give a range of sensitivity from 1.1 to 2.74%. Other cases, such as Ag/MWCNT sensors reported by Nguyen et al [14] and Cui et al [19] showed a sensitivity of 9% at room temperature.…”
Section: Results Of the Sensitivity Measurement Of The Chrsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the table above, we infer that our values of sensitivity (41-171.5) for the sensor containing Pt/MWCNTs (at 250 • C) are much higher than these previously reported in literature (0.025-10) for CNT based systems decorated with other metallic NPs. According to Young and Lin et al [16,17], Au NPs can give a range of sensitivity from 1.1 to 2.74%. Other cases, such as Ag/MWCNT sensors reported by Nguyen et al [14] and Cui et al [19] showed a sensitivity of 9% at room temperature.…”
Section: Results Of the Sensitivity Measurement Of The Chrsmentioning
confidence: 99%
“…MWCNTs decorated with Pt-Ag NPs showed up to 5% more sensitivity than the MWCNTs without NPs, which have only 1.5%. Nanoparticles such as Au, Pt [15][16][17] SnO 2 [18], Ag [14,19], Co [20], ITO [21], Ag/ polyaniline [22] Pd [23] and CdS [10] have been also used on MWCNTs, for ammonia gas detection. So far, techniques such as electron beam evaporation, plasma treatment, sputtering coating, precipitation from the metal salt solution, and thermal evaporation have been employed to decorate MWCNTs [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hegde et al has recently reported a high surface area TiO 2 nanotube array sensor that had lowest detection limit of 100 ppm. In line with standard protocol of validating reproducibility/reversibility characteristics of the sensor, the same was subjected to cycles of three repeated exposure at 100 ppm (fourfold of the represented validation maximum limit) concentration of benzene. The sensor exhibited excellent reversibility as shown in Figure (b; inset) and no sign of response degradation/baseline drift could be observed.…”
Section: Resultsmentioning
confidence: 99%
“…The sensor was designed at 2.4 GHz so that it can be easily compatible with Wi‐Fi and Bluetooth devices, and the sensor geometry can be easily scaled to other frequencies. The design can be also fabricated on low cost substrates such as the work by Lin et al, 18 and can be integrated with new engineering methods to improve the sensitivity of CNT film, 19 for further improved sensing capability.…”
Section: Discussionmentioning
confidence: 99%